2022
DOI: 10.1007/s00535-021-01843-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice guidelines for functional dyspepsia 2021

Abstract: Background Functional dyspepsia (FD) is a disorder that presents with chronic dyspepsia, which is not only very common but also highly affects quality of life of the patients. In Japan, FD became a disease name for national insurance in 2013, and has been gradually recognized, though still not satisfactory. Following the revision policy of Japanese Society of Gastroenterology (JSGE), the first version of FD guideline was revised this time. Method Like pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 107 publications
2
42
1
18
Order By: Relevance
“…Our study showed a very low rate of gastroduodenal ulcers and no upper gastrointestinal malignancies in such patients. The findings support the recommendation of recent Japanese guidelines on the management of FD, which states that esophagogastroduodenoscopy should be considered individually based on the clinical ground rather than being performed indiscriminately ( 20 ). However, these findings should be cautiously interpreted when extrapolated to other populations.…”
Section: Discussionsupporting
confidence: 83%
“…Our study showed a very low rate of gastroduodenal ulcers and no upper gastrointestinal malignancies in such patients. The findings support the recommendation of recent Japanese guidelines on the management of FD, which states that esophagogastroduodenoscopy should be considered individually based on the clinical ground rather than being performed indiscriminately ( 20 ). However, these findings should be cautiously interpreted when extrapolated to other populations.…”
Section: Discussionsupporting
confidence: 83%
“…Utility of abdominal ultrasound for check-up or screening is only recommended for patients at higher risk of abdominal aortic aneurysm [ 17 ]. Lastly, abdominal ultrasonography is not typically recommended for patients presenting with dyspepsia unless there is a presence of red flags [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acid suppression, acotiamide (prokinetic agent) and rikkunshito (Japanese herbal medicine) are recommended for the initial treatment of FD [ 10 ]. The second line treatment includes prokinetic agents except for acotimide and other Japanese herbal medicines except for rikkunshito [ 10 ]. However, patients in our study had persistent symptoms despite the use of these therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of patients in this group were not attenuated by the administration of proton pump inhibitors (PPIs) or prokinetic agents. In the present study, FD was diagnosed according to the criteria of evidence-based clinical guidelines for FD by the Japanese Society of Gastroenterology [ 10 ].…”
Section: Methodsmentioning
confidence: 99%